APLIKASI MIKORIZA DAN PUPUK ORGANIK TERHADAP PERTUMBUHAN TANAMAN KAKAO (Theobroma Cacao L.) DI KABUPATEN GOWA - Idhan, Abubakar (JURNAL ILMIAH PERSPEKTIF, 2010)
ABSTRACT Research aimed to find out the influences of organic fertilizer to cocoa growth , Investigating the effect of micoriza MVA on the growth of cocoa and knowing the interactions between the organic fertilizer application on the growth of mycorrhizal MVA cocoa plant . The research was conducted in the form of factorial experiment which is based on a randomized block design pattern ( RAK ) . The first factor was the provision of organic matter consists of 3 levels , namely : B1 = 5 kg manure , compost fertilizer B2 = cocoa rind 5 Kg , and B3 = skin of cocoa fertilizer + compost leaves 5 Kg and fa gliricidia second factor was the provision of mycorrhizal consisting of : M0 = administration without mycorrhizae , mycorrhizal M1 = administration of 2.5 g / plant , giving mycorrhizal M2 = 5 grams / plant and mycorrhizal M3 = giving as much as 7.5 grams / plant . The results showed that , interaction between applications and mycorrhizal 5 g cocoa skin organic fertilizer ( m2b2 ) gave the best effect on the plant parameters as height and number of leaves . Then the interaction between applications and mycorrhizal 7.5 g organic fertilizer from cocoa skin and leaves gamal ( m3r3 ) gives the best effect on the parameters of leaf area index . Further treatment of the application of mycorrhizal 7.5 g ( m3 ) was given the best results against leaf area , specific leaf area and leaf dry weight of cocoa plants . But in general the provision of treatment of organic materials had not provided any real effect at the time of passage of this research . Key words : Cocoa . Micoriza , Organic Fertilizer